Кардіопротекторний вплив метаболітотропних засобів при фізичному навантаженні інтактних щурів та на фоні коронароспазму - Горчакова, Н. О.; Нагорна, О. О.; Бєленічев, Ігор Федорович; Чекман, І. С.; Горчакова, Н. А.; Нагорная, Е. А.; Беленичев, И. Ф.; Чекман, И. С.; Gorchakova, N. A.; Nagornaya, E. A.; Belenichev, I. F.; Chekman, I. S. (My University, 2018)
Фізичні навантаження під час тренувань та змагань можуть порушити адаптаційні можливості організму, в тому числі діяльності серцевосудинної системи. Ще більш виражені порушення метаболізму і функції серця спостерігають в умовах фізичного навантаження. Мета дослідження – визначити вплив метаболітотропних засобів на працездатність інтактних щурів та при пітуітриновому коронароспазмі, а також на показники ЕКГ і метаболізму міокарду. Експерименти проведені на білих щурах-самцях в умовах рухової гіпоксії, що відтворювали бігом на тредбані при швидкості руху стрічки 50 см/хв при нахилі 50° до повного виснаження. Рухову гіпоксію також моделювали на фоні пітуітринового коронароспазму (пітуітрин вводили внутрішньоочеревинно за 30 хвилин до гіпоксії в дозі 1 ОД/кг). Кардіопротекторну активність метаболітотропних засобів (ангіоліну (50мг/кг), мілдронату, яктону, мексидолу (100 мг/кг)), які вводили внутрішньоочеревинно за 30 хвилин до відтворення рухової гіпоксії, або за 30 хвилин до застосування пітуітрину, визначали за пониженням сегменту ST на ЕКГ та змін біохімічних показників (вмісту маркерів окислювальної модифікації білків – АФГ, КФГ, а також АТФ за загальноприйнятими методами). Физические нагрузки во время тренировок и соревнований могут нарушить адаптационные возможности организма, в том числе деятельности сердечнососудистой системы. Еще более выраженные нарушения метаболизма и функции сердца наблюдаются условиях физической нагрузки. Цель исследования – определение влияния метаболитотропных средств на работоспособность интактных крыс и при питуитриновом коронароспазме, а также на показатели ЭКГ и метаболизма миокарда. Материалы и методы исследования. Эксперименты проведены на белых крысах-самцах в условиях двигательной гипоксии, которую воспроизводили бегом на тредбане при скорости движения ленты 50 см / мин при наклоне 50 ° до полного истощения. Двигательную гипоксию также моделировали на фоне питуитринового коронароспазма (питуитрин вводили внутрибрюшинно за 30 минут до гипоксии в дозе 1 Ед / кг). Кардиопротекторную активность метаболитотропных средств (ангиолина (50 мг / кг), милдроната, яктона, мексидола (100 мг / кг)), которые вводили внутрибрюшинно за 30 минут до воспроизведения двигательной гипоксии, определяли по понижению сегмента ST на ЭКГ и изменениям биохимических показателей (содержания маркеров окислительной модификации белков – АФГ, КФГ, а также АТФ) общепринятыми методами. Результаты и обсуждение. При двигательной гипоксии наблюдалось повышение сегмента ST над изолинией, рост показателей окислительной модификации белков и понижение содержания АТФ, что свидетельствует о развитии оксидативного стресса и понижении образования энергии. Physical loading during training exercises and competitions may influence the organism’ adaption ability, including the cardiovascular system activity. More prominent, cardiac metabolism and function may be changed in the coronary spasm condition with the physical loading. The purpose of the study was to establish the metabolitotropic compounds on the capacity of intact rats and in the conditions of pituitrine coronary vasospasm, ECG and metabolism of myocardial markers. Material and methods. Experiments were conducted on white male rats without line. The physical loading was modulated by running on tredbane with the velocity of ribbon 50 sm / min till exhaustion. There was an experimental series when before the physical loading pituitrine had been administered in dose 1 Unit/kg intraperitoneally for coronary vasospasm modulating. The biochemical experiments were created according to the Methodical recommendation of state Expert Center of the Ministry of Health of Ukraine. The changes of ST segment at ECG and level of ATP, markers of oxidative proteins damage in the rats’ hearts were investigated. The heart tissue was gomogenased in cold acidic isotonic environment (0,15 M KCl) in temperature 4°C by glass gomogenasor. Then the gomogenated tissue put into HCl (0,6 M) to obtain extract without proteins. The drugs have been introduced intraperitoneally in 30 minutes before moving hypoxia modulating in intact rats or before pituitrine administration. Angiolin was introduced in dose 50 mg/kg. mildronate, yakton, mexidol in the dose 100 mg/kg. The rats were decapitated under thiopentalum-natrium injection. Statistic investigations were made with the programs «STATISTICA for Windows 6.0» and «Microsoft Excell 2003». Results and discussion. After the modeling moving hypoxia it was stated in the rats’ hearts decrease of ATP on 27,5%, increase ΣΔST on ECG in 48 times, the level of the markers of oxydative damage of proteins – APhG on 65.%, KPhG on 93.7%. The development of oxidative processes and deficiency of energy was shown. Angiolin increased the duration of running by 53.5%, level ATP on 28%, decrease the content of APhG by 38.3%, KPhG by 44.2%. All other methabolitotropic drugs – mildronat, yakton, mexidol influenced on the biochemical data changes in the same development but in less degree.
Кардиопротекторное влияние метаболитотропных средств при физической нагрузке интактных крыс и на фоне коронароспазма
Cardioprotectoral influence of metabolitotropic measures in physical loading of intact rats and on the coronary vasospasm
Keywords: рухова гіпоксія; пітуітриновий коронароспазм; ангіолін; мілдронат; яктон; мексидол; актопротекція; кардіопротекція; двигательная гипоксия; питуитриновый коронароспазм; ангиолин; милдронат; актопротекция; кардиопротекция; moving hypoxia; pituitrine coronary vasospasm; angiolin; mildronat; yakton; mexidol; actoprotection; cardioprotection